Clinicoetiological and Biochemical Profile of Neonatal Convulsions - Rajesh Kumar Yadav; I K Sharma; Durgesh Kumar; K M Shukla; Kalbe Jawwad; Vineet Chaturvedi (International Journal of Medical Research and Review, 2015)
Introduction: Neonatal seizures may present in 1-2% of term to almost 20% in preterm infants. Hypoxic ischemic encephalopathy, sepsis and bacterial meningitis are common causes. Biochemical abnormality and intra cranial bleed is also quiet common in this age. Aim of our study was to observe clinical presentation, to find common etiological factors and analysis of associated biochemical abnormality in newborn presented with neonatal convulsions in our hospital.Methods: Prospective hospital based observational study. From January 2014 to December 2014, total 168 newborns admitted with convulsions or developed convulsions during hospitalization, 154 were included in the study. After taking complete history and appropriate physical examination, blood sample was collected before instituting specific therapy. Investigations advised to all were complete blood count, sepsis screen, blood sugar, serum electrolytes. CSF study, serum bilirubin, USG cranium, CT scan or MRI was also ordered when indicated.Results: Cumulative frequency of neonatal convulsion in our study was 5.52%. Perinatal asphyxia was most common etiological factor in term or post term babies and presentation of seizures was early, intra cranial bleed and metabolic abnormality was common cause of convulsions in premature babies and presentation of seizure was somewhat late. Subtle seizure was most common type of fits followed by clonic type of seizures. Hypocalcemia was most common biochemical derangement.Conclusion: hypoxic ischemic encephalopathy was most common etiology of neonatal convulsions, presented with convulsions within 72 hours of life and subtle seizure and focal clonic or multifocal clonic was most common seizure type.